Marbling score, cholesterol, and physical–chemical content of male Bali beef fed fermented pineapple peel - Bulkaini, Bulkaini; Dahlanuddin, Dahlanuddin; Ariana, Tirta; Kisworo, Djoko; Maskur, Maskur; Mastur, Mastur (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The study was conducted to determine the marbling score, fat and meat color, cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and physical–chemical content of male Bali beef fed fermented pineapple peel. Materials and Methods: Twelve heads of male Bali cattle with an initial weight of 168.46 ± 11.95 kg were put into individual cages at random based on a completely randomized design with three treatments and four heads of Bali cattle as replicates, namely T0 = NG + (39% MC + 61% RB + 0% fermented pineapple peel); T1 = NG + (10% MC + 70% RB + 20% fermented pineapple peel with yeast culture); and T2 = NG + (15% MG + 65% RB + 20% pineapple peel fermented by lactic acid bacteria). The sample of Bali cattle meat used in testing the research variables was the LD muscle, with as many as 24 samples for each treatment. The data were analyzed based on the analysis of variance using the Statistical Product and Service Solutions software program, following Duncan’s test with 5% confidence. Results: The results showed that the treatment T2 could increase the marbling quality of the meat from 2.58% to 4.00%. The cholesterol content (80 mg/100 gm), HDL (60 mg/100 gm), LDL (10 mg/100 gm), water-holding capacity (36.10%), cooking loss (29.16%), tenderness/shear force (4.08 kg/cm2), crude protein (22.99%), crude fat (4.23%), and meat collagen (1.65%) were determined. Conclusions: Adding 20% of fermented pineapple peel by lactic acid bacteria to the ration can improve the quality of marbling, produce cholesterol, and the physical–chemical value of meat that meets the Indonesian National Standard. J. Adv. Vet. Anim. Res., 9(3): 419–431, September 2022 http://doi.org/10.5455/javar.2022.i610